Analisis Tingkat Bahaya Erosi di Sub DAS Manday - Fung, Nyit; Soeryamassoeka, Stefanus Barlian; Gunarto, Danang (Universitas Tanjungpura, 2026)
Erosion is the process by which soil particles are detached and transported from their original location to other areas, primarily driven by water and wind, through the breakdown of soil aggregates (dispersion) and surface runoff. Continuous erosion can lead to sedimentation in rivers, reducing their capacity to carry water and increasing the risk of flooding during periods of high rainfall. However, scientific studies on erosion in the Manday sub-watershed remain limited. This study aims to analyze the extent of erosion occurring in the Manday Sub-Watershed using the Universal Soil Loss Equation (USLE) method combined with Geographic Information Systems (GIS), classify the erosion hazard level (EHL) in the Manday Sub-Watershed, and produce a map of the distribution of erosion hazard levels (EHL) in the Manday Sub-Watershed. The parameters used include the erosivity factor (R), soil erodibility (K), slope length and gradient (LS), land cover (C), and land conservation measures (P). The results of the study show that erosion in the Manday Sub-Watershed amounts to 101,491.44 tons/ha/year, with five erosion hazard levels (EHL) classified: very low, low, moderate, high, and very high, with the very low category covering 176,966.41 ha (56.95%) and the low category covering 92. 773.49 ha (29.86%), while the moderate category accounted for 5.67% (17,618.21 ha), severe for 3.35% (10,397.92 ha), and very severe for 4.17% (12,971.30 ha). Mapping the distribution of erosion hazard levels (TBE) shows that areas with higher TBE are generally on steep slopes with minimal vegetation cover. This mapping underscores the need for targeted land management in high-risk areas to mitigate erosion impacts.